The Effect of Financial Literacy and Peers on Consumptive Behavior in Students of the Economic Education Study Program, University of Riau - Diana Septiani; Almasdi Syahza; R. M. Riadi (CV. Rayyan Dwi Bharata, 2023)
The problem in this study is the low financial literacy and the high influence of peers which have an impact on the consumptive behavior of economic education students. This study aims to determine whether there is influence of financial literacy and peers on consumptive behavior in students of the economics education study program. This research was conducted at the Economics Education Study Program, with a population of 258 students and a sample of 91 respondents. The data collection instrument used was a questionnaire. The results of data analysis using multiple linear regression and hypothesis testing and concluded that financial literacy, peers, and influence on student consumptive behavior. From the results of the analysis of the significant value between financial literacy and consumptive behavior, it can be seen from the tcount 4.915 ttable 1.987 and a significant value (0.000 0.05). And for the significant value between peers on consumptive behavior seen from the tcount 6.744 ttable 1.987 and significant (0.000 0.05). Simultaneously (F test) is indicated by Fcount 26.818 3.10 Ftable with a significant value of 0.000 0.05. Thus, it can be concluded that financial literacy and peers have a positive and simultaneous influence on consumptive behavior in students of the Economics Education Study Program, University of Riau.